2021
DOI: 10.3390/ijerph18084270
|View full text |Cite
|
Sign up to set email alerts
|

Using Digital Platforms to Promote Blood Donation: Motivational and Preliminary Evidence from Latin America and Spain

Abstract: The lack of blood donors is a global problem that prevents the demand for blood prompted by an ageing population and increased life expectancy from being met. The aim of this study was to conduct an initial exploration of the reasons for using digital platforms in blood donation. Using a Theory of Planned Behaviour (TPB) framework, microdata for 389 participants from Latin American countries and Spain, and Partial Least Square-Structural Equation Modelling (PLS-SEM), the study obtained three main prediction pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 99 publications
(71 reference statements)
1
17
0
2
Order By: Relevance
“…Together with its extension, the theory of planned behavior (TPB) (Ajzen, 1991 ), it is one of the most established theories used to predict blood donation behavior (Ferguson, 1996 ; Godin et al, 2007 ; Masser et al, 2009 ). Recently, Torrent‐Sellens et al ( 2021 ) used the TPB to explain participation in digital blood donation community platforms. We assume that the TAM is suitable for studying blood donors' acceptance of DASSs.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Together with its extension, the theory of planned behavior (TPB) (Ajzen, 1991 ), it is one of the most established theories used to predict blood donation behavior (Ferguson, 1996 ; Godin et al, 2007 ; Masser et al, 2009 ). Recently, Torrent‐Sellens et al ( 2021 ) used the TPB to explain participation in digital blood donation community platforms. We assume that the TAM is suitable for studying blood donors' acceptance of DASSs.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…There are different parameters that drive or discourage people from donating blood [22]. To advertise, encourage, attract, and retain blood donors, several approaches have been investigated using ICT and smart devices.…”
Section: Related Workmentioning
confidence: 99%
“…The health centres where the data were collected are associated with that institution. Moreover, as in other eHealth studies carried out by the leader of this research team [37], the study followed the Checklist for Reporting Results of Internet E-Surveys (CHERRIES) guidelines [51].…”
Section: Datamentioning
confidence: 99%
“…Furthermore, self-identity was In general, TPB has been used to model blood donation intent and behaviour [33]. For example, to determine the return behaviour of blood donors [34,35] and understand different underlying motives that influence the intention to perform voluntary blood donation [36][37][38][39][40]. Regarding re-donation behaviour, Wevers et al [34] reported that the act of donating blood stimulates re-donation behaviour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation